2021
DOI: 10.1002/ueg2.12105
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease integral care units: Evaluation of a nationwide quality certification programme. The GETECCU experience

Abstract: Background One of the most valued targets in inflammatory bowel disease (IBD) is for physicians to provide and patients to receive a high‐level quality of care. This study aimed to evaluate the implementation of a nationwide quality certification programme for IBD units. Methods Identification of quality indicators (QI) for IBD Unit certification was based on Delphi methodology that selected 53 QI, which were subjected to a normalisation process. Selected QI were then used in the certification process. Coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…However, our results show that both native and immigrant populations have full access to biologic therapies under the universal healthcare coverage provided by Spain's public health service, and low socioeconomic status is therefore unlikely to have contributed to differences in prescription patterns in this study. On the other hand, clinical practice among ENEIDA researchers is fairly uniform due to Spanish program of certification of quality of care at inflammatory bowel disease units (53), which sets the standards of care in IBD all over the country. An alternative explanation is that immigrant patients may have a distinctive disease course.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show that both native and immigrant populations have full access to biologic therapies under the universal healthcare coverage provided by Spain's public health service, and low socioeconomic status is therefore unlikely to have contributed to differences in prescription patterns in this study. On the other hand, clinical practice among ENEIDA researchers is fairly uniform due to Spanish program of certification of quality of care at inflammatory bowel disease units (53), which sets the standards of care in IBD all over the country. An alternative explanation is that immigrant patients may have a distinctive disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to the development of UC, including genetic factors, environmental factors, bacterial infections, and hormonal drugs [ 30 , 31 ]. Several studies have shown that intestinal barrier dysfunction and disruption of immune homeostasis within the intestinal mucosa are important causes of UC under pathological conditions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are in the upper limit of the wide range of incidence previously described [10,14,28], ranging from 0.95 [29] to 100 per 1000 [15]. The universal access to health care within the National Health System in Spain (less than 3% of IBD patients with private insurance never use public services [30]) and the adherence of most centres to the nationwide certification programme in IBD [26] provide homogeneity to the cohort, minimizing potential bias in the clinical characteristics. We did not calculate the comparative incidence of COVID-19 between the IBD cohort and data obtained from the general population because the identification of cases did not use the same methodology.…”
Section: Discussionmentioning
confidence: 80%
“…However, data on hospitalisation, severe COVID-19, ICU admission and death from the general population are similar to our cohort and we did not find differences in specific outcomes between these two searching strategies; therefore, this bias is probably small. On the other hand, the majority of participant centres were certified IBD units that had open access to their outpatient clinics, nurse-led advice lines and/or emails for emergencies as mandatory quality criteria [26]. Second, this study, including only the first wave of an ongoing pandemic, is observational and cannot establish causation or account for unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation